Dilemmas about the scope of the Act on Prevention of Domestic Violence from a human rights perspective - Darko Simović (Srpska Politička Misao)
The adoption of the Act on Prevention of Domestic Violence was driven by the creation of a more effective legal framework for the protection of victims of domestic violence, and, therefore, also by the alignment of the legal system of the Republic of Serbia with international obligations. The main novelties include multi-sectoral cooperation and primarily preventive nature of the law. However, from its very adoption, it has been pointed to its noticeably repressive character, as well as to provisions with potentially harmful impacts. Hence, this paper represents a contribution to the discussion on the importance and scope of the solutions provided for in the Act on Prevention of Domestic Violence. On the one hand, it points to major novelties intended to contribute to a more effective prevention of domestic violence. On the other hand, it questions the constitutionality and appropriateness of some of the legal solutions, arguing that, in particular respects, the lawmaker had to use a wiser and more subtle approach to conceptualising the provisions of this law.